Pulsed electrosynthesis of glycolic acid through polyethylene terephthalate upcycling over a mesoporous PdCu catalyst - Shu Han; Lizhi Sun; Dongping Fan; Ben Liu (Nature Communications)
Abstract Electrocatalytic upcycling of polyethylene terephthalate (PET) plastics offers a promising and sustainable route that not only addresses serious waste pollution but also produces high value-added chemicals. Despite some important achievements, their activity and selectivity have been slower than needed. In this work, pulsed electrocatalysis is employed to engineer chemisorption properties on a lamellar mesoporous PdCu (LM-PdCu) catalyst, which delivers high activity and stability for selective electrosynthesis of high value-added glycolic acid (GA) from PET upcycling under ambient conditions. LM-PdCu is synthesized by in situ nucleation and attachment strategy along assembled lamellar templates, whose stacked morphology and lamellar mesoporous structure kinetically accelerate selective desorption of GA and expose fresh active sites of metal catalysts for continuous electrocatalysis at pulsed mode. This strategy thus delivers GA Faraday efficiency of >92% in wide potential windows, yield rate of reaching 0.475 mmol cm–2 h–1, and cycling stability of exceeding 20 cycles for electrocatalytic PET upcycling. Moreover, pulsed electrocatalysis discloses good electrocatalytic performance for scaled-up GA electrosynthesis from real bottle waste plastics. This work presents a sustainable route for selective electrosynthesis of value-added chemicals through upcycling of various waste feedstocks.